Performance management: A systematic review of processes in elite sport and other high performance domains - Molan, C.; Kelly, S.; Arnold, R.; Matthews, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The desire to achieve success within elite sport has seen various sports look beyond the application of sport sciences and coaching to management-led processes. Performance management has been identified as a process that impacts how athletes, coaches and support staff contribute to elite sport success. Due to the limited research in this area within elite sport and the potential transferability of processes from other settings, there is considerable merit is examining how performance is managed across alternative high performance domains, where individuals or teams must also work under pressure to deliver high standards of performance, e.g. military, surgical medicine and performing arts. The aim of this study was to conduct a systematic review of performance management within elite sport and other high performance domains. Methods: Electronic database keyword searches and reference tracing were conducted to identify published, English language, peer reviewed articles with original empirical evidence. Further eligibility criteria related to the type of performance management process and performance domain were applied. Title, abstract, and full text screening was undertaken by two reviewers, and inter-rater reliability statistics were calculated. Following data extraction, thematic synthesis enabled the organisation of key performance management factors into `descriptive themes`; and the development of higher level `analytical themes`. Results: A total of 17 studies from a possible 12,196 were included in the review. Five analytical themes (and 15 descriptive themes) representing factors associated with effective performance management in high performance domains emerged: collaboration, execute and review performance, leadership, manage the performance environment, and recruitment and retention of staff. Research design and sample characteristics for each study were also reported. Discussion: This review details prominent features of performance management that are required to perform consistently at high levels in intensely pressurised environments. These identified factors range across person, operational and system levels and also highlight how factors from alternative high performance domains could be harnessed to enhance the performance management process within elite sport organisations or high performance units. Further research is needed to develop our understanding of both the theoretical components and the operationalisation of performance management within elite sport.